Investigating the sustainability of Open Universities: Models, opportunities, and challenges (Journal of Applied Learning and Teaching, 2025)
With the increased interest towards lifelong learning and the need for a shift from traditional to open universities, several questions were raised about the sustainability of open universities in this rapidly changing technological era and the ongoing geopolitical tension worldwide. To address this research gap, this study conducts a focus group discussion with nine open university leaders on sustainability models, opportunities and challenges of open universities. The results reveal that most of the open universities rely on government funds, which is considered the most guaranteed yet fragile model, in addition to tuition fees. The results further reveal that open universities go beyond the financial dimension to also cover technological and pedagogical dimensions when sustaining themselves, where most open universities are relying on their own developed software, open-source software, and Open Educational Resources to reduce course development costs.